Integrating p300 functions in HTLV-1 transcription initiation - Luebben, Whitney R., author; Nyborg, Jennifer K., advisor; Stargell, Laurie, committee member; Laybourn, Paul, committee member; Prenni, Jessica, committee member; Quackenbush, Sandra, committee member (Colorado State University. Libraries, 2014)
The HTLV-1 provirus overcomes a repressive chromatin environment for efficient transcription of its genome. This is accomplished by the robust recruitment of the coactivator protein, p300, to the viral enhancer sites through interactions with DNA bound pCREB and the viral transactivating protein, Tax. Recruitment of p300 to the HTLV-1 promoter results in histone acetylation and nucleosome depletion from the promoter region in the presence of the histone chaperone, Nap1. To study the histone acetylation requirements for Nap1-dependent nucleosome disassembly, we utilized immobilized in vitro assembled chromatin templates containing site specific K→R mutations within the N-terminal tails of the histones. Through these studies, we identified histone H3, lysine 14 as the functionally relevant acetylation site for Nap1-dependent nucleosome disassembly. Additionally, we found a significant correlation between nucleosome disassembly from the HTLV-1 promoter and acetylation-dependent transcription activation. These studies suggest that nucleosome disassembly is a prerequisite for transcription activation, as nucleosome disassembly creates a nucleosome free region within the HTLV-1 promoter, allowing for the subsequent recruitment of Pol II and general transcription machinery for activation of transcription. The identification of a single and specific acetyl-lysine residue led us to the hypothesis that the p300 acetyl-lysine binding domain (bromodomain) was involved in HTLV-1 transcription activation through recognition of H3K14ac. To test this hypothesis, we utilized a p300 bromodomain deletion mutant and a CBP/p300 specific bromodomain inhibitor, (SGC-CBP30), to investigate the involvement of the p300 bromodomain in HTLV-1 transcription activation. Importantly, we found that the p300 bromodomain is not involved in the initial recruitment of the coactivator to the chromatin template as previously proposed, rather the bromodomain functions after recruitment to the promoter and following acetylation of the histone tails. These findings are consistent with a role for the p300 bromodomain in nucleosome disassembly and uncover a novel function for the bromodomain in gene activation.
Keywords: histone acetylation; transcription; p300; nucleosome; HTLV-1; bromodomain